Heterogeneity of TP53 Mutations and P53 Protein Residual Function in Cancer: Does It Matter? - Monti, Paola; Menichini, Paola; Speciale, Andrea; Cutrona, Giovanna; Fais, Franco; Taiana, Elisa; Neri, Antonino; Bomben, Riccardo; Gentile, Massimo; Gattei, Valter; Ferrarini, Manlio; Morabito, Fortunato; et al. (Frontiers in Oncology, 2020)
The human TP53 locus, located on the short arm of chromosome 17, encodes a tumour suppressor protein which functions as a tetrameric transcription factor capable of regulating the expression of a plethora of target genes involved in cell cycle arrest, apoptosis, DNA repair, autophagy, and metabolism regulation. TP53 is the most commonly mutated gene in human cancer cells and TP53 germ-line mutations are responsible of the development of the cancer-prone Li-Fraumeni syndrome. When mutated, the TP53 gene generally presents missense mutations, which can be distributed throughout the coding sequence, although they are found most frequently in the central DNA binding domain of the protein. TP53 mutations may represent an important prognostic and predictive marker in cancers. The presence of a TP53 mutation does not necessarily implies a complete P53 inactivation; in fact, mutant P53 proteins are functionally heterogeneous and are classified as loss of function, partial function, temperature sensitive, with altered specificity, wild type-like, super-transactivating, dominant or gain of function. Different models have been used to explore these never-ending facets of TP53 mutations, generating abundant experimental data on their functional impact. Here, we briefly review the studies on the different functional effects of TP53 mutations and the possible implications for clinical outcome. The focus shall be on Chronic Lymphocytic Leukemia (CLL), which also has generated considerable discussion on the role of TP53 mutations for therapy decisions.